1996
DOI: 10.1007/bf00019099
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of transketolase (EC 2.2.1.1) active in the Calvin cycle of spinach chloroplasts

Abstract: A cDNA encoding the Calvin cycle enzyme transketolase (TKL; EC 2.2.1.1) was isolated from Sorghum bicolor via subtractive differential hybridization, and used to isolate several full-length cDNA clones for this enzyme from spinach. Functional identity of the encoded mature subunit was shown by an 8.6-fold increase of TKL activity upon induction of Escherichia coli cells that overexpress the spinach TKL subunit under the control of the bacteriophage T7 promoter. Chloroplast localization of the cloned enzyme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…4), suggesting that p76 is a polypeptide derived from a TKL in C. littorale. This inference is further supported by the fact that the molecular mass of 76 kDa resembles those of TKL subunits (around 74 kDa) reported in higher plants, such as Craterostigma plantagineum (Bernacchia et al 1995) and spinach chloroplast (Flechner et al 1996, Teige et al 1998. By Western blot analysis (Fig.…”
Section: Resultssupporting
confidence: 52%
“…4), suggesting that p76 is a polypeptide derived from a TKL in C. littorale. This inference is further supported by the fact that the molecular mass of 76 kDa resembles those of TKL subunits (around 74 kDa) reported in higher plants, such as Craterostigma plantagineum (Bernacchia et al 1995) and spinach chloroplast (Flechner et al 1996, Teige et al 1998. By Western blot analysis (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Using gel ®ltration and sedimentation analysis Villafranca and Axelrod [165] demonstrated that TK extracted from spinach leaves apparently exists in monomeric form with a subunit molecular weight of approximately 100 kDa. However, the recent determination of the sequence of spinach TK [36] revealed that the subunit molecular weight is approximately 74 kDa, similar to that of other plant TKs.…”
Section: Oligomeric Structurementioning
confidence: 78%
“…f S. uvarum (type strain: CBS 395) is regarded as a synonym of S. bayanus (type strain: CBS 380) (Barnett, 1992) and their MET2 sequences are identical (Hansen and Kielland-Brandt, 1994). Flechner et al, 1996;Schenk et al, 1997), sequences from different ascomycetes may not be true orthologues. b Where multiple accession numbers are listed the sequences overlap.…”
Section: Comparison Of Kluyveromyces Results To Theoretical Predictionsmentioning
confidence: 97%